Global Initiative for Asthma Strategy 2021: Executive Summary and Rationale for Key Changes. Issue 1 (12th January 2022) - Reddel, Helen K.; Bacharier, Leonard B.; Bateman, Eric D.; Brightling, Christopher E.; Brusselle, Guy G.; Buhl, Roland; Cruz, Alvaro A.; Duijts, Liesbeth; Drazen, Jeffrey M.; FitzGerald, J. Mark; Fleming, Louise J.; Inoue, Hiromasa; et al.
Abstract: The Global Initiative for Asthma (GINA) Strategy Report provides clinicians with an annually updated evidence‐based strategy for asthma management and prevention, which can be adapted for local circumstances (e.g., medication availability). This article summarizes key recommendations from GINA 2021, and the evidence underpinning recent changes. GINA recommends that asthma in adults and adolescents should not be treated solely with short‐acting β2 ‐agonist (SABA), because of the risks of SABA‐only treatment and SABA overuse, and evidence for benefit of inhaled corticosteroids (ICS). Large trials show that as‐needed combination ICS–formoterol reduces severe exacerbations by ≥60% in mild asthma compared with SABA alone, with similar exacerbation, symptom, lung function, and inflammatory outcomes as daily ICS plus as‐needed SABA. Key changes in GINA 2021 include division of the treatment figure for adults and adolescents into two tracks. Track 1 (preferred) has low‐dose ICS–formoterol as the reliever at all steps: as needed only in Steps 1–2 (mild asthma), and with daily maintenance ICS–formoterol (maintenance‐and‐reliever therapy, "MART") in Steps 3–5. Track 2 (alternative) has as‐needed SABA across all steps, plus regular ICS (Step 2) or ICS–long‐acting β2 ‐agonist (Steps 3–5). For adults with moderate‐to‐severe asthma, GINA makes additional recommendations in Step 5 for add‐on long‐acting muscarinic antagonists and azithromycin, with add‐on biologic therapies for severe asthma. For children 6–11 years, new treatment options are added at Steps 3–4. Across all age groups and levels of severity, regular personalized assessment, treatment of modifiable risk factors, self‐management education, skills training, appropriate medication adjustment, and review remain essential to optimize asthma outcomes.